Use of the Modified Shuttle Walk Test During Inpatient Pediatric Cystic Fibrosis Pulmonary Exacerbation Treatment. Issue 3 (July 2018) - Paranjape, Shruti M.; Carson, Kathryn A.; Demissie, Seifu M.; Loosen, Holly; Vela, Kerry; Mogayzel, Peter J.
Abstract : Purpose: Exercise improves pulmonary function and physical conditioning in cystic fibrosis. Exercise capacity was assessed in the inpatient setting to determine whether pulmonary exacerbation treatment with intravenous antibiotics, airway clearance, and exercise would improve exercise capacity independently of lung function. Methods: Exercise capacity was measured at hospital admission and hospital discharge by numbers of completed shuttles using the Modified Shuttle Walk Test (MSWT). Resting heart rate, oxyhemoglobin saturation, and assessments of breathlessness and perceived exertion were measured before and after exercise. Pulmonary function tests were obtained on the day of hospital admission and within 2 weeks of hospital discharge. Results: Fifty-four children performed the MSWT at hospital admission and hospital discharge. Exercise capacity increased by 15.9% during hospitalization, and lung function, measured as a percentage of the predicted forced expiratory volume in 1 second, by 15.7% during intravenous antibiotic treatment. Children with higher exercise capacity showed greater lung function ( r = 0.42, P < .001) and lower preexercise resting heart rate at both hospital admission ( r = −0.25, P = .03) and hospital discharge ( r = −0.30, P = .007). No differences in breathlessness or perceived exertion were observed. Conclusions: Exercise capacity and physical conditioning improved during early pulmonary exacerbation treatment. The MSWT can be used safely to assess changes in exercise capacity during hospitalization.